The effect of oil pulling in comparison with chlorhexidine and other mouthwash interventions in promoting oral health: A systematic review and meta-analysis - Jong, Freda Jia Xin *; Ooi, Der Jiun; Teoh, Siew Li (Wiley, 2024)
Objectives A meta-analytic review was performed to critically synthesize the evidence of oil pulling on improving the parameters of gingival health, plaque control and bacteria counts against chlorhexidine and other mouthwash or oral hygiene practices.